The Effects of Pythagorean Self-Awareness Intervention on Patients with Panic Disorder: A Randomized Controlled Trial - Zarenti, Maria; Bacopoulou, Flora; Chrousos, George; Pipelias, Panagiotis; Mantikas, Vasileios; Sideris, Panagiotis; Panagoulias, Eustathios; Michou, Maria; Kokka, Ioulia; Darviri, Christina (Archives of Clinical and Medical Case Reports, 2026)
Introduction: Panic Disorder constitutes one of the most common anxiety disorders, and is characterized by recurrent, unexpected panic attacks accompanied by multiple psychophysiological symptoms. Previous studies examining the effects of cognitive-behavioral interventions and other stress management techniques have yielded mixed findings. Materials and Methods: This randomized controlled study aimed to evaluate the effects of the Pythagorean Self-Awareness Intervention (PSAI), a novel, non-pharmaceutical, stress management technique, on symptom severity, quality of life, emotional and cognitive characteristics, lifestyle factors, and stress-related biological markers in patients with panic disorder. Standardized questionnaires were administered at baseline and 8 weeks after the intervention to assess quality of life, perceived stress, depression, health locus of control, and anxiety. Sleep quality, lifestyle parameters, and hair cortisol concentrations were also evaluated. Results: A total of 60 patients were randomly assigned to either the intervention group (n=30), which participated in the 8-week PSAI program, or the control group (n=30). Participants in the PSAI group demonstrated significant improvements across most outcomes. Large effect sizes (> 0.5) were observed for internal locus of control, perceived stress, and cortisol levels. Improvements were also found in secondary outcomes.